2013
DOI: 10.1007/s00239-013-9548-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Internal Transcribed Spacer 2 (ITS2) of the Ribosomal DNA (rDNA) Cluster in Calyptratae (Diptera: Schizophora) and its Implications for Molecular Phylogenetic Analyses

Abstract: The internal transcribed spacer 2 (ITS2) of the eukaryotic ribosomal DNA (rDNA) cluster plays an essential role in processing of the ribosomal RNA, which is primarily accomplished by the secondary structures acquired by the molecule after transcription. Two possible structural conformation models have been proposed for the ITS2 region, the "ring model" and the "hairpin model," and the former has been widely used in many molecular phylogenetic analyses incorporating structural information available to date. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…For the region ITS2 , the nomenclature adopted is based on the works of Young and Coleman () and Marinho et al. (, , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the region ITS2 , the nomenclature adopted is based on the works of Young and Coleman () and Marinho et al. (, , ).…”
Section: Resultsmentioning
confidence: 99%
“…For the ITS2 region, we used a combined approach of de novo and homology‐based modelling, comprising: (1) in silico prediction based on thermodynamic parameters with the mfold software (Zuker, ); (2) comparison with previously published structures for D. melanogaster (Young and Coleman, ) and some species of the Calliphoridae and Mesembrinellidae families (Marinho et al., , , ); and (3) comparison among the structures predicted for all species and the establishment of a common folding pattern.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the ITS2 sequences were folded in silico , further studies are needed to confirm that these structures are accurate (Eddy, ; Marinho et al , ). Overall, the ITS2 structures were consistent with the conserved patterns observed by Coleman (), loosely corresponding to the four‐domain model predicted for ITS2 (Schultz et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…ITS 2 plays an essential role in the maturation of the pre-ribosomal RNA as its secondary structure contained the cleavage sites for the pre-rRNA processing (Marinho et al, 2013). Previous studies showed that ITS 2 is a good molecular marker to phylogenetic inferences among families, subfamilies, and especially as a molecular marker in lower taxonomic groups as genera and species.…”
Section: Introductionmentioning
confidence: 99%